Analisis Faktor-Faktor yang Mempengaruhi Produksi Jeruk di Kenagarian Kototinggi Kecamatan Gunuang Omeh Kabupaten 50 Kota Menggunakan Regresi Linear Berganda - leni rahayu; meira parma dewi (Journal of Mathematics UNP, 2019)
Abstract–The production centre of oranges in 50 Kota Regency, Kototonggi Subdistrict. The production of oranges has a fluctuation every year.Thei purposei is to observe the most signifikant factor which influences the production of the oranges at Kototinggi Subditrict, Gunuang Omeh District, 50 Kota Regency. The instrument was a questionnaire given directly to 100 orange farmers in Kototinggi Subdistrict and the data included primary data. The analysis used is multi linier regresion analysis. The most significant factors of oranges production in Kototinggi Subdistrict are farming land area (x1) , amount of fertilizer (x3),  amount of pesticide (x4),  diseases and pest (x5) with the level of error 10 %Keywords–Orange, Multiple Linear Regression Analysis, Factor of Production